Pengaruh Ketebalan Koating TiO2 Dan Konsentrasi Pelarut Etanol Terhadap Voltase Dye Sensitized Solar Cell (DSSC) Menggunakan Ekstrak Buah Senggani (Melastoma Candidum D. Don) - Ranti, Aisyah Dewi; Amri, Amun; Yelmida, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Solar cell is an active element that converts light energy into electrical energy by photovoltaic effect. Dye Sensitized Solar Cell (DSSC)is the into third generation that is solar cells. The aims of this study is to determine the effect of TiO2 layer thickness and the concentration of ethanol to the DSSC voltage. The study began by making a dye solution of 20 grams of Senggani dissolved in methanol, acetic acid and distilled water. FTO glass coating was then performedusing TiO2 that was dissolved in ethanol, then deposited by spin coating and sintering method using furnace. The next step was the manufacture of electrolytic solution, a carbon electrode manufacture and assembly of DSSC. The test results using a UV-Vis absorbance showed that the dye solution containing anthocyanin at 520 nm absorption. DSSC was achieved the higher voltage due the thickness of TiO2. The best result (0.9524 Volt / cm2) by variation of TiO2thickness (≈ 387 m) with ethanol absolute (without dilution). XRD test showed that TiO2 anatase was anatase phase. The morphology test show that the coating of TiO2 with ethanolsolvent have a particles size than coating with distilled water solvent. The adhesion test showed the adhesion coating on the FTO glass was at good qualifications 2B.Keywords: DSSC, FTO glass, TiO2 coating thickness, TiO2